Pandemi Covid 19 dan Pasar Saham di Indonesia: Studi Kasus Kebijakan PPKM Skala Mikro - Wahyu Irawan; Rizka Aulia; Daniel W Kristia; Dimaciela V Sekarlangit; H Hersugondo Hersugondo (Soegijapranata Catholic University, 2022)
The COVID-19 pandemic that has hit various countries has caused a decline in various sectors: one of them is the economic sector. Social restriction policies affect the level of economic activity and stock prices on major stock market indexes. This study aims to examine the impact of COVID-19 on the stock market in Indonesia with the implementation of the Micro-Scale PPKM Policy. This research used secondary data with a purposive sampling technique to obtain 45 companies indexed LQ45. Correlation and regression analysis were used in this study. The results showed that: 1) the growth rate of confirmed cases of COVID-19 had a negative effect on the Indonesian stock market. 2) the recovery rate from COVID-19 has a positive influence on the Indonesian stock market. 3) mortality growth rate is negatively related to stock market returns in Indonesia. Empirical evidence obtained from the results of this study states that COVID-19 has a significant effect on the Indonesian stock market.